2009
DOI: 10.1111/j.1447-0756.2008.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal treatment for glassy cell carcinoma of the uterine cervix

Abstract: Glassy cell carcinoma of the uterine cervix is a rare form of cervical cancer that is characterized by aggressiveness and poor prognosis because of its rapid growth, its frequent distant metastases, and its relative resistance to conventional treatment modalities including surgery, radiotherapy, and chemotherapy. We report here a case of glassy cell carcinoma of the uterine cervix that was successfully treated with radical surgery followed by radiation therapy and combination chemotherapy with paclitaxel and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…[8][9][10][11] Nasu et al reported a case of glassy cell carcinoma treated using conventional radiation therapy and six courses of triweekly PC chemotherapy. 12 We also considered that adjuvant PC chemotherapy is effective for GCC.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Nasu et al reported a case of glassy cell carcinoma treated using conventional radiation therapy and six courses of triweekly PC chemotherapy. 12 We also considered that adjuvant PC chemotherapy is effective for GCC.…”
Section: Discussionmentioning
confidence: 99%
“…A recidiva local geralmente ocorre no ápice vaginal e a disseminação pélvica ocorre para paramétrio, ovários e linfonodos paraórticos. 2 Devido à raridade da doença e à falta de estudos prospectivos, o manejo da doença não está especificamente definido. 12 Em estágios iniciais, o câncer tipo glassy cell de colo uterino pode ser tratado por histerectomia com linfadenectomia pélvica associada ou não à radioquimioterapia adjuvante.…”
Section: Discussionunclassified
“…21Y23 The mean age at diagnosis is approximately 10 years earlier than that in patients affected by the more common uterine squamous cell carcinoma or adenocarcinoma. 21 In the 19 previously reported patients, the histologic type was squamous cell carcinoma in 11 cases, adenocarcinoma in 6 cases, and adenosquamous in 1 case. Usually, it presents at an advanced stage at the time of diagnosis, with the development of pelvic and distant metastasis being common.…”
Section: Case Reportmentioning
confidence: 93%
“…20,21 Some authors have made an association between this tumor and pregnancy; however, others did not find any association between them. 20,21 Some authors have made an association between this tumor and pregnancy; however, others did not find any association between them.…”
Section: Case Reportmentioning
confidence: 99%